PEMBERIAN ASI EKSLUSIF, SUPLEMEN VITAMIN A DAN ASUPAN SENG DENGAN RISIKO KEJADIAN PNEUMONIA PADA ANAK BALITA DI PUSKESMAS PUUWATU KECAMATAN PUUWATU KOTA KENDARI - Rita Irma; Sunaryo Sunaryo; Akbar Toruntju S. (Jurnal Kesehatan Manarang, 2016)
Pneumonia is the leading cause of death in children. Many factors can influence the increased incidence of pneumonia in young children, Among them are age, sex, nutritional status, low birth weight, immunization status, Exclusive breastfeeding, and vitamin A. This study aims to determine the relationship of exclusive breastfeeding, supplements vitamin A, and zinc intake with the incidence of pneumonia in children under five in sub-district Puskesmas Puuwatu Kendari. This study uses a case-control design. Take place at sub-district Puskesmas Puuwatu Kendari. A sample of 32 samples taken using P = prevalence of LBW infants (0.092%), d = absolute precision (10%), Z = confidence interval (95% = 1.96). Taken with accidental sampling technique, and performed on samples Matching namely age, where the age of the sample of cases and controls were age 1 to 5 years. Data analysis was conducted to see the value Odds Ratio (OR), Odds Ratio (OR) = ad/bc with confidence interval (CI) = 95%. The results showed that young children who are not breastfed Exclusive 3.4 times greater risk of pneumonia compared with exclusive breastfeeding of children under five, which marked the value of OR = 3.40. Infants and children who do not complete vitamin A supplementation 2.4 times greater risk of developing pneumonia than children under five who complete vitamin A supplementation, which marked the value of OR = 2.49. Infants and children who lack their zinc intake were 2.4 times greater risk of pneumonia compared with toddlers sufficient intake of tin, which is marked with OR = 2.43. This study concluded that children who are not breastfed Exclusive have an increased risk of pneumonia. Supplementation with vitamin A complete and sufficient zinc intake in children under five among children could reduce the incidence of pneumonia.